2020
DOI: 10.1111/boc.202000066
|View full text |Cite
|
Sign up to set email alerts
|

Early endocytosis as a key to understanding mechanisms of plasma membrane tension regulation in filamentous fungi

Abstract: Background Information. Two main systems regulate plasma membrane tension (PMT) and provide a close connection between the protoplast and the cell wall in fungi: turgor pressure and the actin cytoskeleton. These systems work together with the plasma membrane focal adhesion to the cell wall and their contribution to fungal cell organization and physiology has been partially studied. However, it remains controversial in model filamentous ascomycetes and oomycetes and even less investigated in filamentous basidio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…These steps correspond to: the stage of formation of endocytic patches (primary vesicles covered in a rigid actin scaffold) and early endosomes; the stage of labeling late endosomes/early vacuoles; and the stage of labeling tonoplasts of vacuoles-lysosomes. Similar results were obtained in our previous studies for Rhizoctonia solani and some species of wood-decaying basidiomycetes (Kamzolkina et al, 2017; Mazheika et al, 2020a, b). We have proposed two important things related to fungal endocytosis and fungal cell organization.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…These steps correspond to: the stage of formation of endocytic patches (primary vesicles covered in a rigid actin scaffold) and early endosomes; the stage of labeling late endosomes/early vacuoles; and the stage of labeling tonoplasts of vacuoles-lysosomes. Similar results were obtained in our previous studies for Rhizoctonia solani and some species of wood-decaying basidiomycetes (Kamzolkina et al, 2017; Mazheika et al, 2020a, b). We have proposed two important things related to fungal endocytosis and fungal cell organization.…”
Section: Introductionsupporting
confidence: 91%
“…Our previous publication showed that hyphae of Rhizoctonia solani under hypertonic conditions could shrink in cross section with a loss of up to 15% in hyphae diameter (Mazheika et al, 2020a). The cell wall of fungi is elastic, the protoplast is attached to it from the inside through multiple sites of focal adhesion, therefore, when cells lose water, hyphae, like yeast cells, shrink entirely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations